Preoperative recombinant human erythropoietin in anemic surgical patients - Monk, Terri G (BioMed Central, 2004)
Preoperative anemia in a surgical patient predisposes to poor outcomes and allogeneic blood transfusions. As an alternative to transfusions, pharmacologic management of preoperative anemia with recombinant human erythropoietin (rHuEPO) has been well studied in many different types of surgery. rHuEPO, when used alone or in combination with preoperative autologous blood donation before elective surgery, stimulates erythropoiesis and helps to avoid or reduce the need for allogeneic blood transfusions. The clinical evidence on preoperative use of rHuEPO in orthopedic, cardiac, and cancer surgery, as well as in bloodless surgery, is reviewed.